Gaze Path Stimulation in Retrospective Think-Aloud - Aulikki Hyrskykari; Saila Ovaska; Pävi Majaranta; Kari-Jouko Räihä; Merja Lehtinen (Bern Open Publishing, 2008)
For a long time, eye tracking has been thought of as a promising method for usability testing. During the last couple of years, eye tracking has finally started to live up to these expectations, at least in terms of its use in usability laboratories. We know that the user's gaze path can reveal usability issues that would otherwise go unnoticed, but a common understanding of how best to make use of eye movement data has not been reached. Many usability practitioners seem to have intuitively started to use gaze path replays to stimulate recall for retrospective walk through of the usability test. We review the research on thinkaloud protocols in usability testing and the use of eye tracking in the context of usability evaluation. We also report our own experiment in which we compared the standard, concurrent think-aloud method with the gaze path stimulated retrospective think-aloud method. Our results suggest that the gaze path stimulated retrospective think-aloud method produces more verbal data, and that the data are more informative and of better quality as the drawbacks of concurrent think-aloud have been avoided.